Differential enrichment of bacteria and phages in the vaginal microbiomes in PCOS and obesity: shotgun sequencing analysis - Zheng, Senlin; Chen, Huimin; Yang, Hongyi; Zheng, Xulan; Fu, Tengwei; Qiu, Xiaoyan; Wang, Meiqin (Frontiers in Microbiomes, 2024)
Previous studies have shown that vaginal bacteria are associated with polycystic ovary syndrome (PCOS) and obesity in women. However, the specific differences in vaginal microbiota between these conditions remain unclear. In this study, we aimed to investigate the contribution of dysregulated vaginal microbiota to PCOS and obesity by analyzing the vaginal microbiota in reproductive-aged women with and without PCOS and in obese and non-obese women using shotgun sequencing. Swab specimens were collected from four groups of subjects, including PCOS and obese, PCOS and non-obese, non-PCOS and obese, and non-PCOS and non-obese. A total of 333 bacteria and 24 viruses/phages were identified to species level in this study. The clustering result showed that non-PCOS and non-obese individuals have a similar "healthy" vaginal microbiome, while both obesity and PCOS were associated with microbial dysbiosis. There were 26 bacterial species and 6 phages/viruses that showed significant differences in abundance between groups. The pathobionts, Streptococcus pyogenes, Leptospira santarosai, Citrobacter amalonaticus, Listeria ivanovii, and Clostridium perfringens were significantly lower abundance or not detected in the non-PCOS and non-obese group. The abundance of Lactobacillus, Pseudomonas bacteria and their corresponding phages were positively correlated. In addition to Lactobacillus bacteria, lactobacillus phage and pseudomonas phage/virus were identified as indicators of a healthy vaginal microbiome. The differentially enriched bacteria in the PCOS and obesity groups were completely different.Overall, this study confirms that PCOS and obesity have different enrichment of bacteria and viruses/phages, and both conditions are associated with microbial dysbiosis. Our findings show for the first time that vaginal phage diversity is associated with a healthy vaginal microbiota, while dysbiosis of the vaginal microbiota is associated with a decrease in phages with increased bacterial diversity.